Evaluation of drought indices to identify tolerant genotypes in common bean bush (Phaseolus vulgaris L.) - Alefsi David SÁNCHEZ-REINOSO; Gustavo Adolfo LIGARRETO-MORENO; Hermann RESTREPO-DÍAZ (Journal of Integrative Agriculture, 2020)
Drought is one of the major abiotic stresses often causing negative impacts on bean crops in the Andean region in Colombia. An experiment under the greenhouse conditions was carried out to assess the effect of a prolonged drought period (15 days) at two different phenological stages (vegetative or reproductive) on grain yield and yield components of five bush bean cultivars (ICA-Cerinza, Bachue, NUA35, Bianca, and Bacatá). Nine tolerance indices including stress susceptibility index (SSI), tolerance (TOL), mean productivity (MP), geometric mean productivity (GMP), stress tolerance index (STI), yield stability index (YSI), yield index (YI), Harmonic mean (HM), and drought sensitivity index (DSI) were calculated based on grain yield under non-stressed (YP) and drought (YS) conditions. Based on the different drought indices, genotypes ICA-Cerinza and NUA35 had the best performance under drought conditions in both studied phases, which reflected in a reduction of grain yield ~≤40%. The biplot analysis also showed a clear superiority of these two genotypes at both phenological stages. Results also showed that SSI was more effective to identify genotypes less affected by drought. The above results allowed us to conclude that ICA-Cerinza and NUA35 may be considered for agricultural areas where long periods of water deficit are expected and can be used in breeding programs for drought tolerance.